A porous tantalum layer implant material and its preparation method and application

By wrapping the mixture of iron powder, aluminum powder and tantalum powder on the surface of the titanium-based implant, and performing thermal isostatic pressure and pickling treatment under high temperature and high pressure conditions, the problems of difficult preparation of porous tantalum layers and unstable quality in the prior art are solved, and efficient and safe preparation of porous tantalum layer implant materials are achieved.

CN119733834APending Publication Date: 2025-04-01HEFEI BOYA MAITE BIOMATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928045.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art method for preparing porous tantalum on the surface of titanium-based implants has problems such as harsh preparation conditions, high cost, high processing difficulty, difficult structural control, and unstable quality.

Method used

The porous tantalum layer implant material is obtained by mixing iron powder, aluminum powder and tantalum powder in a specific proportion, wrapped around the surface of the titanium substrate implant, and subjected to thermal isostatic pressure under high temperature and high pressure conditions, followed by pickling treatment to remove unnecessary metal compounds.

Benefits of technology

The preparation of a porous tantalum layer with adjustable porosity and interconnected interconnection is achieved, and the osteogenic performance and biofixation effect of titanium-based implants are improved. Combined with the increase in strength, the safety and reliability of the implant is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733834A_ABST
    Figure CN119733834A_ABST
Patent Text Reader

Abstract

The present application proposes a porous tantalum layer implant material and its preparation method and application, which relates to the field of medical material technology. First, iron powder, aluminum powder and tantalum powder are obtained according to the weight percentage of 50% to 70%, 10% to 20% and 15% to 40% respectively, and the pseudo alloy powder is evenly mixed. Then, the pseudo alloy powder is wrapped on the surface of the titanium base implant with titanium foil, and the surface is placed in a mold with the same shape as the titanium base implant, and the green body is pressed. Further, the green body is hot isostatically pressed under high temperature and high pressure conditions to obtain a first component. Finally, the first component is pickled to remove the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer to obtain a porous tantalum layer implant material. The method uses the pseudo alloy powder corrosion method to prepare porous tantalum, which can obtain porous tantalum with adjustable porosity and interconnected, and improves the bonding strength between the porous tantalum layer and the titanium substrate, ensuring its safety, reliability and implant effectiveness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of medical materials, and in particular to a porous tantalum layer implant material and a preparation method and application thereof. Background Art

[0002] Titanium and titanium alloys have been widely used in the field of orthopedic implants due to their excellent biocompatibility and mechanical properties. They have good corrosion resistance, are not easily affected by body fluids and chemically react or degrade, and are safe and reliable under long-term implant conditions. Titanium has a similar elastic modulus to human bones, which can effectively reduce the stress shielding effect and promote bone integration, which is crucial for patients who need to carry implants for a long time or even for life. Titanium has good processing and forming capabilities, and can be customized to produce implants of various shapes and sizes according to different medical needs, providing great flexibility for clinical treatment.

[0003] However, titanium and titanium alloys are highly inert and do not react chemically with surrounding tissues, which limits their ability to bond with bone tissue. Titanium-based implants may take longer to achieve effective integration with surrounding bone tissue, affecting the patient's recovery speed and the ultimate treatment effect. Porous tantalum performs well in promoting bone healing and improving the success rate of long-term implants. Its three-dimensional interconnected pore structure provides an ideal growth environment for new bone cells, accelerates the bone integration process, and improves the biological fixation effect between the implant and the host bone. Tantalum material itself also has excellent biocompatibility and corrosion resistance, can maintain stable performance in the body for a long time, and reduce the risk of inflammatory reactions and other adverse tissue reactions.

[0004] However, the current methods for preparing porous tantalum on the surface of titanium-based implants include: 3D printing, laser cladding, plasma spraying, explosion welding, etc. These methods have the following disadvantages: harsh preparation conditions, high cost, difficult processing, difficult structure control, and unstable quality. Summary of the invention

[0005] The present application provides a porous tantalum layer implant material and a preparation method and application thereof to solve the above-mentioned problems.

[0006] In a first aspect, the present application provides a method for preparing a porous tantalum layer implant material, the method comprising the following steps:

[0007] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, mix them evenly to obtain pseudo alloy powder, wherein the weight percentage ranges of iron powder, aluminum powder and tantalum powder are 50% to 70%, 10% to 20%, and 15% to 40% respectively;

[0008] Step 2: Wrapping the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, placing it in a mold with the same shape as the titanium-based implant, and pressing to obtain a green body, wherein the green body includes the titanium-based implant and the pseudo alloy powder;

[0009] Step 3: performing hot isostatic pressing on the green body under high temperature and high pressure conditions to obtain a first component, wherein the first component includes: a titanium base implant and a pseudo alloy layer;

[0010] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and metal compounds thereof in the pseudo alloy layer to obtain a porous tantalum layer implant material.

[0011] In an optional embodiment, the method further comprises:

[0012] Using pure water to perform ultrasonic cleaning on the first component after the pickling treatment for multiple times to remove residual acid on the surface of the first component;

[0013] The power range of the ultrasonic cleaning is 30kHz to 50kHz, and the time range is 5min to 25min.

[0014] In an optional embodiment, the weight percentage ranges of iron powder, aluminum powder and tantalum powder are: 53% to 57%, 12% to 14%, and 30% to 35%, respectively.

[0015] In an optional embodiment, in step 3, the temperature range of the hot isostatic pressing treatment is 550° C. to 650° C., the pressure range is 150 MPa to 200 MPa, and the holding time range is 2 h to 4 h.

[0016] In an optional embodiment, in step 3, the temperature range of the hot isostatic pressing treatment is 630° C. to 650° C., the pressure range is 180 MPa to 200 MPa, and the holding time range is 3 h to 4 h.

[0017] In an optional embodiment, in step 4, the volume ratio of the pickling solution used for pickling the first component is: 1% to 5% hydrofluoric acid, 5% to 15% nitric acid, and 1% to 5% lactic acid, and the pickling time is 2 hours.

[0018] In an optional embodiment, in step 4, the volume ratio of the pickling solution used for pickling the first component is: 4% to 5% hydrofluoric acid, 13% to 15% nitric acid, 4% to 5% lactic acid, and the pickling time is 2 hours.

[0019] In a second aspect, the present application proposes a porous tantalum layer titanium-based implant material, wherein the porous tantalum layer implant material is prepared according to the preparation method described in any one of the above-mentioned first aspects.

[0020] In an optional embodiment, the porous tantalum layer implant material includes a porous tantalum layer and a titanium base implant, the pore size range of the porous tantalum layer is 200μm to 800μm, the thickness range of the porous tantalum layer is 200μm to 1000μm, the porosity range of the porous tantalum layer is 12% to 35%, the elastic modulus of the porous tantalum layer is 24GPa to 56GPa, and the bonding force range of the porous tantalum layer and the titanium base implant is 15.6MPa to 32.3MPa.

[0021] In the second aspect, the present application proposes the use of the porous tantalum layer implant material as described in any one of the second aspects above in the preparation of tantalum layer orthopedic implants, wherein the porous tantalum layer implant material is used to prepare any one of the following tantalum layer orthopedic implants: implants, plates, acetabular cups, hip implants, knee implants, shoulder implants, and ankle implants.

[0022] The present application proposes a porous tantalum layer implant material and its preparation method and application. First, iron powder, aluminum powder and tantalum powder are obtained respectively by weight percentage, and mixed evenly to obtain pseudo alloy powder. The weight percentage ranges of iron powder, aluminum powder and tantalum powder are 50% to 70%, 10% to 20%, and 15% to 40% respectively. Then, the pseudo alloy powder is wrapped on the surface of the titanium base implant with titanium foil, and placed in a mold with the same shape as the titanium base implant, and pressed to obtain a green body. Further, the green body is subjected to hot isostatic pressing under high temperature and high pressure conditions to obtain a first component. Finally, the first component is pickled to remove the titanium foil, iron, aluminum and metal compounds thereof in the pseudo alloy layer to obtain a porous tantalum layer implant material. The method includes the following advantages:

[0023] (1) The porous tantalum is prepared by the pseudo alloy powder corrosion method, and a porous tantalum layer with adjustable porosity and interconnected can be obtained;

[0024] (2) The hot isostatic pressing method is used to achieve metallurgical bonding between the tantalum-containing layer and the titanium substrate, with a bonding strength of more than 15 MPa, which is 4% to 115% higher than the hydroxyapatite coating that has been used in clinical practice, ensuring its safety and reliability as an orthopedic implant;

[0025] (3) The pickling method can not only completely remove iron, aluminum and their metal compounds, but also fine-tune the porosity and pore morphology of the porous tantalum layer by controlling the ratio in the pickling solution;

[0026] (4) The obtained porous tantalum layer has a low elastic modulus, which can effectively avoid the stress shielding effect of traditional high modulus materials during implantation, further improving the effectiveness of implantation;

[0027] (5) The porosity of the obtained porous tantalum layer is between 12% and 35%, which is suitable for bone tissue ingrowth;

[0028] (6) The thickness of the obtained porous tantalum layer can be adjusted between 200 μm and 1000 μm, which is convenient for manufacturing various orthopedic implants. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0030] Figure 1 This is a scanning electron microscope image of a porous tantalum layer implant material prepared in Example 5 provided in the examples of the present application. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0032] Titanium and titanium alloys have been widely used in the field of implantable medical devices due to their excellent biocompatibility and mechanical properties. Titanium and titanium alloys have good corrosion resistance, are not easily affected by body fluids and chemically react or degrade, and are safe and reliable under long-term implant conditions. In addition, titanium has a similar elastic modulus to human bones, which can effectively reduce the stress shielding effect and promote bone integration, which is crucial for patients who need to carry implants for a long time or even for life. Titanium has good processing and forming capabilities, and can be customized to produce implants of various shapes and sizes according to different medical needs, providing great flexibility for clinical treatment.

[0033] However, titanium and titanium alloys are highly inert and do not react chemically with surrounding tissues. This ensures their stability and safety in the human body, but also limits their ability to integrate with bone tissue to a certain extent. Titanium implants may take longer to achieve effective integration with surrounding bone tissue, affecting the patient's recovery speed and the ultimate treatment effect.

[0034] Porous tantalum is an excellent material for orthopedic repair and reconstruction surgery because it performs well in promoting bone healing and improving the success rate of long-term implantation. The three-dimensional interconnected pore structure of porous tantalum provides an ideal growth environment for new bone cells. These pores can guide the inward growth of bone cells and accelerate the bone integration process, thereby improving the biological fixation effect between the implant and the host bone. In addition, tantalum material itself has excellent biocompatibility and corrosion resistance, can maintain stable performance in the body for a long time, and reduce the risk of inflammatory response and other adverse tissue reactions.

[0035] The methods and problems currently proposed for preparing porous tantalum layers on titanium-based implant surfaces include:

[0036] (1) 3D printing: Pure tantalum powder is mixed with a forming agent and sent to a 3D printer for printing. A porous tantalum layer is then obtained through degreasing, vacuum sintering, cooling and heat treatment. This method can precisely control the porous structure, but the process is relatively complex, the production efficiency is low, and the cost is high.

[0037] (2) Laser cladding: A layer of high-purity tantalum powder is pre-laid on the substrate surface, and then a metal tantalum layer is prepared by laser cladding. This method can achieve metallurgical bonding, but the surface morphology and pore size of the layer are difficult to control, and microcracks may occur. The equipment investment cost is high and the process is complicated.

[0038] (3) Plasma spraying: By changing the distance between the anode and the substrate to control the thickness and porosity of the porous layer, porous tantalum layers with different pore gradients can be prepared. However, this method has poor bonding strength, is prone to peeling, and it is difficult to obtain a uniform tantalum layer for prostheses with complex structures.

[0039] (4) Explosive welding: The method of preparing titanium-tantalum-platinum composite plates by explosive welding can form a solid-state bond between titanium and tantalum. However, this method is difficult to produce thin composite plates, is not conducive to reducing the amount of tantalum, is difficult to control costs, has unstable quality, and has noise and shock wave pollution.

[0040] Based on this, the present application proposes a new preparation method, by mixing iron powder, aluminum powder and tantalum powder, and preparing a pseudo alloy on a titanium matrix through hot isostatic pressing technology, and further removing iron and aluminum through acid etching method to obtain a porous surface, thereby improving the osteogenic performance and biological fixation effect of titanium-based implants.

[0041] In a first aspect, an embodiment of the present application provides a method for preparing a porous tantalum layer implant material, the method comprising the following steps:

[0042] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively according to weight percentage, mix them evenly to obtain pseudo alloy powder, and the weight percentage ranges of iron powder, aluminum powder and tantalum powder are 50% to 70%, 10% to 20%, and 15% to 40% respectively.

[0043] In order to obtain a porous tantalum layer on the surface of a titanium-based implant without using existing 3D printing or electrochemical methods, the present application can successfully prepare a porous tantalum layer on the surface of a titanium-based implant. First, a pseudo-alloy layer needs to be wrapped on the surface of the titanium-based implant, and then other metals or metal compounds except tantalum in the pseudo-alloy layer are removed to successfully prepare a porous tantalum layer on the surface of the titanium-based implant.

[0044] Based on this, first obtain the pseudo alloy powder wrapped on the surface of the titanium-based implant. In addition to tantalum powder, the pseudo alloy powder also contains iron powder and aluminum powder. This is because the mixture of iron powder, aluminum powder and tantalum powder can form a continuous metal structure in tantalum, which is convenient for forming cavities after pickling to obtain a porous tantalum layer.

[0045] Wherein, the weight percentage of iron powder, aluminum powder and tantalum powder in the pseudo alloy powder ranges from 50% to 70%, 10% to 20%, and 15% to 40%, respectively. Exemplarily, by weight percentage, the pseudo alloy powder may contain 50% iron powder, 55% iron powder, 60% iron powder, 65% iron powder, 70% iron powder, etc., the pseudo alloy powder may contain 10% aluminum powder, 13% aluminum powder, 15% aluminum powder, 17% aluminum powder, 20% aluminum powder, etc., the pseudo alloy powder may contain 15% tantalum powder, 20% tantalum powder, 25% tantalum powder, 30% tantalum powder, 35% tantalum powder, 40% tantalum powder, etc.

[0046] In a preferred embodiment of the present application, the weight percentages of iron powder, aluminum powder and tantalum powder are in the range of 53% to 57%, 12% to 14%, and 30% to 35% respectively. For example, by weight percentage, the pseudo alloy powder may contain 53% iron powder, 54% iron powder, 57% iron powder, etc., the pseudo alloy powder may contain 12% aluminum powder, 13% aluminum powder, 14% aluminum powder, etc., and the pseudo alloy powder may contain 30% tantalum powder, 32% tantalum powder, 35% tantalum powder, etc.

[0047] Step 2: Wrap the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, put it into a mold with the same shape as the titanium-based implant, and press it to obtain a green body, which includes the titanium-based implant, pseudo alloy powder and titanium foil.

[0048] Since the metal powder cannot be directly connected or coated with the surface of the titanium-based implant, the present application uses titanium foil to wrap the pseudo-alloy powder on the surface of the titanium-based implant, puts it into a mold with the same shape as the titanium-based implant, and presses it to obtain a green body.

[0049] The thickness and size of the titanium foil should be determined according to the size and shape of the titanium-based implant actually used, and the embodiments of the present application are not limited thereto.

[0050] Specifically, the pseudo alloy powder is first evenly coated or spread on the surface of the titanium-based implant to facilitate subsequent bonding and reaction. The prepared titanium foil is wrapped on the surface of the titanium-based implant coated with the pseudo alloy powder. It is necessary to ensure that the titanium foil is closely attached to the alloy powder on the surface of the titanium-based implant so that the powder and the titanium base can be well bonded during the subsequent heat treatment process.

[0051] Step 3: Performing hot isostatic pressing on the green body under high temperature and high pressure conditions to obtain a first component, wherein the first component includes: a titanium base implant and a pseudo alloy layer.

[0052] Under high temperature and high pressure conditions, the green embryo forms a strong interface connection through the diffusion of atoms. This connection is similar to smelting or solid phase reaction in the metallurgical process, so it is called metallurgical bonding. In this bonding process, tantalum and titanium matrix can achieve strong bonding between the material interfaces under high temperature and high pressure conditions, improving the overall performance and reliability between tantalum and titanium matrix.

[0053] Hot Isostatic Pressing (HIP) is a method of forming high-density billets (or parts) by applying isostatic pressure in all directions to powders or sintered billets (or parts) to be compacted in a sealed container at high temperature and pressure, using high-pressure gas as the medium. In the processing of metal materials such as titanium alloys, the hot isostatic pressing process generally does not have a liquid phase. Through high temperature and high pressure composite load combined with mold technology, loose powder can be densified into high-performance metal parts with complex structures in a relatively short time.

[0054] Specifically, the green body is subjected to hot isostatic pressing under high temperature and high pressure conditions to obtain a first component, wherein the first component includes a titanium-based implant and a pseudo alloy layer, wherein the pseudo alloy layer contains at least tantalum, iron and aluminum metals, and metal compounds thereof, and titanium foil for surface wrapping, wherein the metal compound may be TiFe, Ti3Al, etc. During the hot isostatic pressing process, eutectic phase and Fe2+ can be formed between iron, aluminum and tantalum. 2 The (Ta, Al) reinforcement phase can connect pure iron, pure aluminum and pure tantalum phases with a certain strength to ensure structural strength. Through HIP treatment, solid-state diffusion bonding under high temperature and high pressure environment can achieve metallurgical bonding between tantalum and titanium matrix and ensure the bonding strength between the two.

[0055] In an optional embodiment of the present application, in the above step 3, the temperature range of the hot isostatic pressing treatment used in the embodiment of the present application is 550°C to 650°C, the pressure range is 150MPa to 200MPa, and the holding time range is 2h to 4h. Exemplarily, the temperature of the hot isostatic pressing treatment can be 550°C, 600°C, 650°C, etc., the pressure can be 150MPa, 170MPa, 175MPa, 200MPa, etc., and the holding time can be 2h, 3h, 4h, etc.

[0056] In a preferred embodiment of the present application, in the above step 3, the temperature range of the hot isostatic pressing treatment is 630°C to 650°C, the pressure range is 180MPa to 200MPa, and the holding time range is 3h to 4h. Exemplarily, the temperature of the hot isostatic pressing treatment can be 630°C, 640°C, 650°C, etc., the pressure can be 180MPa, 190MPa, 200MPa, etc., and the holding time can be 3h, 4h, etc.

[0057] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and metal compounds thereof in the pseudo alloy layer to obtain a porous tantalum layer implant material.

[0058] After hot isostatic pressing, the pseudo alloy powder has achieved metallurgical bonding with the titanium base implant. In order to obtain a porous tantalum layer, the embodiment of the present application removes the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer by pickling to obtain a porous pure tantalum structure. The above metal compounds can be TiFe, Ti 3 Al, etc. This is because the titanium foil wrapped on the surface reacts with iron powder, aluminum powder, etc. to produce corresponding metal compounds.

[0059] Specifically, the first component is pickled to remove titanium foil, iron, aluminum and metal compounds thereof in the pseudo alloy layer to obtain a porous tantalum layer implant material, which includes a porous tantalum layer and a titanium-based implant.

[0060] The pickling solution used for pickling includes hydrofluoric acid, nitric acid and lactic acid. The fluorine ions in hydrofluoric acid have a special corrosion-accelerating effect on titanium, which can remove the titanium foil on the surface. Nitric acid has strong acid and strong oxidizing properties, which can completely remove iron, aluminum and their metal compounds. Lactic acid forms a loose layer by acting on the corrosion products, preventing hydrofluoric acid from corroding the titanium foil to produce TiF 4 、TiF6 2- Complex accumulation.

[0061] By changing the ratio of the pickling solution, the iron, aluminum, and alloys and intermetallic compounds formed during the hot isostatic pressing process are completely dissolved, leaving only the porous pure tantalum structure to ensure biological safety. At the same time, the pickling method can not only completely remove iron, aluminum and their metal compounds, but also fine-tune the porosity and void morphology of porous tantalum by controlling the ratio in the pickling solution.

[0062] In an optional embodiment of the present application, in step 4, the volume ratio of the pickling solution for pickling the first component is: 1% to 5% hydrofluoric acid, 5% to 15% nitric acid, and 1% to 5% lactic acid, and the pickling time is 2 hours. Exemplarily, the pickling solution may contain 1% hydrofluoric acid, 2% hydrofluoric acid, 3% hydrofluoric acid, 4% hydrofluoric acid, 5% hydrofluoric acid, etc., the pickling solution may contain 5% nitric acid, 7% nitric acid, 10% nitric acid, 13% nitric acid, 15% nitric acid, etc., the pickling solution may contain 1% lactic acid, 2% lactic acid, 3% lactic acid, 4% lactic acid, 5% lactic acid, etc.

[0063] In a preferred embodiment of the present application, in step 4, the volume ratio of the pickling solution for pickling the first component is: 4% to 5% hydrofluoric acid, 13% to 15% nitric acid, 4% to 5% lactic acid, and the pickling time is 2 hours. Exemplarily, the pickling solution may contain 4% hydrofluoric acid, 5% hydrofluoric acid, etc., the pickling solution may contain 13% nitric acid, 14% nitric acid, 15% nitric acid, etc., the pickling solution may contain 4% lactic acid, 5% lactic acid, etc.

[0064] In an optional embodiment, the above preparation method further comprises:

[0065] The first component after the pickling treatment is ultrasonically cleaned multiple times with pure water to remove residual acid on the surface of the first component.

[0066] The power range of ultrasonic cleaning is 30kHz to 50kHz, and the time range is 5min to 25min.

[0067] Preferably, the working parameters of ultrasonic cleaning are an ultrasonic frequency of 40 kHz and a time of 20 min.

[0068] Further optionally, after the ultrasonic treatment is completed, the ultrasonically treated component can be dried at a temperature ranging from 50° C. to 150° C. for a time ranging from 5 h to 10 h, preferably at a temperature of 100° C. for 6 h.

[0069] In a second aspect, an embodiment of the present application provides a porous tantalum layer titanium-based implant material, and the porous tantalum layer implant material is prepared according to the preparation method described in any one of the above-mentioned first aspects.

[0070] In an optional embodiment of the present application, the above-mentioned porous tantalum layer implant material includes a porous tantalum layer and a titanium base implant, the pore size range of the porous tantalum layer is 200μm~800μm, the thickness range of the porous tantalum layer is 200μm~1000μm, the porosity range of the porous tantalum layer is 12%~35%, the elastic modulus of the porous tantalum layer is 24GPa~56GPa, and the bonding force range of the porous tantalum layer and the titanium base implant is 15.6MPa~32.3MPa.

[0071] The porous tantalum layer of the obtained porous tantalum layer implant material has a low elastic modulus, which can effectively avoid the stress shielding effect of traditional high modulus materials during implantation, and further improve the effectiveness of implantation. The porosity of the porous tantalum layer of the obtained porous tantalum layer implant material is between 12% and 35%, which is suitable for bone tissue growth, and the thickness of the porous tantalum layer can be adjusted between 200μm and 1000μm, which is convenient for manufacturing implants suitable for various usage scenarios such as implants, bone screws, and hip cups.

[0072] In the third aspect, an embodiment of the present application proposes an application of a porous tantalum layer implant material as described in the second aspect above in the preparation of a tantalum layer orthopedic implant. Titanium and its alloys have good biocompatibility. The present application prepares a porous tantalum layer on the surface of a titanium-based implant, which can be widely used in the preparation of implants for hip joints, knee joints, shoulder joints, ankle joints, etc., can promote cell adhesion, proliferation and differentiation, and exhibit good osteogenic activity.

[0073] Based on this, the above-mentioned porous tantalum layer implant material is used to prepare any one of the following tantalum layer orthopedic implants: implants, bone plates, acetabular cups, hip joint implants, knee joint implants, shoulder joint implants, and ankle joint implants.

[0074] Next, a porous tantalum layer implant material and its preparation method and application proposed in this application are described in detail in combination with specific embodiments. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can be obtained from commercial sources. The percentages used in the following embodiments, unless otherwise specified, are all weight percentages.

[0075] Example 1

[0076] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, mix them evenly to obtain pseudo alloy powder, the weight percentage of iron powder, aluminum powder and tantalum powder is: 50% iron powder, 10% aluminum powder, 40% tantalum powder;

[0077] Step 2: Wrap the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, put it into a mold with the same shape as the titanium-based implant, and press it to obtain a green body;

[0078] Step 3: hot isostatic pressing the green body under high temperature and high pressure conditions to obtain a first component, wherein the hot isostatic pressing processing parameters are: temperature of 550° C., pressure of 150 MPa, and holding time of 4 hours;

[0079] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer, and the first component after pickling is ultrasonically cleaned multiple times with pure water to remove residual acid on the surface of the first component to obtain a porous tantalum layer implant material. The volume ratio of the pickling solution used in the pickling treatment is: 1% hydrofluoric acid, 5% nitric acid, and 5% lactic acid.

[0080] Example 2

[0081] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, mix them evenly to obtain pseudo alloy powder, the weight percentage of iron powder, aluminum powder and tantalum powder is: 70% iron powder, 15% aluminum powder, 15% tantalum powder;

[0082] Step 2: Wrap the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, put it into a mold with the same shape as the titanium-based implant, and press it to obtain a green body;

[0083] Step 3: hot isostatic pressing the green body under high temperature and high pressure conditions to obtain a first component, wherein the hot isostatic pressing processing parameters are: temperature of 600° C., pressure of 175 MPa, and holding time of 3 h;

[0084] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer, and the first component after pickling is ultrasonically cleaned multiple times with pure water to remove residual acid on the surface of the first component to obtain a porous tantalum layer implant material. The volume ratio of the pickling solution used in the pickling treatment is: 3% hydrofluoric acid, 10% nitric acid, and 3% lactic acid.

[0085] Example 3

[0086] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, mix them evenly to obtain pseudo alloy powder, the weight percentage of iron powder, aluminum powder and tantalum powder is: 60% iron powder, 20% aluminum powder, 20% tantalum powder;

[0087] Step 2: Wrap the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, put it into a mold with the same shape as the titanium-based implant, and press it to obtain a green body;

[0088] Step 3: hot isostatic pressing the green body under high temperature and high pressure conditions to obtain a first component, wherein the hot isostatic pressing processing parameters are: temperature of 650° C., pressure of 200 MPa, and holding time of 2 h;

[0089] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer, and the first component after the pickling treatment is ultrasonically cleaned multiple times with pure water to remove the residual acid on the surface of the first component to obtain a porous tantalum layer implant material. The volume ratio of the pickling solution used in the pickling treatment is: 5% hydrofluoric acid, 15% nitric acid, and 1% lactic acid.

[0090] Example 4

[0091] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, mix them evenly to obtain pseudo alloy powder, the weight percentage of iron powder, aluminum powder and tantalum powder is: 53% iron powder, 12% aluminum powder, 35% tantalum powder;

[0092] Step 2: Wrap the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, put it into a mold with the same shape as the titanium-based implant, and press it to obtain a green body;

[0093] Step 3: hot isostatic pressing the green body under high temperature and high pressure conditions to obtain a first component, wherein the hot isostatic pressing processing parameters are: temperature of 630° C., pressure of 200 MPa, and holding time of 4 h;

[0094] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer, and the first component after the pickling treatment is ultrasonically cleaned multiple times with pure water to remove the residual acid on the surface of the first component to obtain a porous tantalum layer implant material. The volume ratio of the pickling solution used in the pickling treatment is: 4% hydrofluoric acid, 13% nitric acid, and 4% lactic acid.

[0095] Example 5

[0096] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, and mix them evenly to obtain pseudo alloy powder, wherein the weight percentage of iron powder, aluminum powder and tantalum powder is: 57% iron powder, 13% aluminum powder and 30% tantalum powder;

[0097] Step 2: Wrap the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, put it into a mold with the same shape as the titanium-based implant, and press it to obtain a green body;

[0098] Step 3: hot isostatic pressing the green body under high temperature and high pressure conditions to obtain a first component, wherein the hot isostatic pressing processing parameters are: temperature of 640° C., pressure of 190 MPa, and holding time of 3 h;

[0099] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer, and the first component after the pickling treatment is ultrasonically cleaned multiple times with pure water to remove the residual acid on the surface of the first component to obtain a porous tantalum layer implant material. The volume ratio of the pickling solution used in the pickling treatment is: 5% hydrofluoric acid, 14% nitric acid, and 4% lactic acid.

[0100] Example 6

[0101] Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, mix them evenly to obtain pseudo alloy powder, the weight percentage of iron powder, aluminum powder and tantalum powder is: 54% iron powder, 14% aluminum powder, 32% tantalum powder;

[0102] Step 2: Wrap the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, put it into a mold with the same shape as the titanium-based implant, and press it to obtain a green body;

[0103] Step 3: hot isostatic pressing the green body under high temperature and high pressure conditions to obtain a first component, wherein the hot isostatic pressing processing parameters are: temperature of 650° C., pressure of 180 MPa, and holding time of 4 hours;

[0104] Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and their metal compounds in the pseudo alloy layer, and the first component after the pickling treatment is ultrasonically cleaned multiple times with pure water to remove the residual acid on the surface of the first component to obtain a porous tantalum layer implant material. The volume ratio of the pickling solution used in the pickling treatment is: 5% hydrofluoric acid, 15% nitric acid, and 5% lactic acid.

[0105] Example 7

[0106] Based on the porous tantalum layer implant materials prepared in the above-mentioned embodiments 1 to 6, performance characterization experiments were conducted. Specifically, the thickness and pore size of the porous tantalum layer implant materials were measured by microscopic observation after dissection, the porosity of the porous tantalum layer implant materials was measured by liquid immersion method, the bonding force of the porous tantalum layer implant materials was measured by adhesion test, and the elastic modulus of the porous tantalum layer implant materials was measured by compression test. The characterization results are shown in Table 1.

[0107] It should be noted that the various methods used for the above-mentioned performance characterization are conventional means used by those skilled in the art and will not be described in detail here.

[0108] Table 1 Performance characterization results of porous tantalum layer implant materials prepared in Examples 1 to 6

[0109]

[0110] It can be seen from Table 1 that a porous tantalum layer (porosity range 12% to 35%) with adjustable porosity and interconnected can be prepared by the pseudo-alloy powder corrosion method in Examples 1 to 6 of the present application, and the pore size range in the porous tantalum layer is 200 μm to 800 μm, which is suitable for bone tissue growth. At the same time, the thickness range of the porous tantalum layer can be adjusted between 200 μm and 1000 μm, which is convenient for manufacturing various implants.

[0111] Secondly, the hot isostatic pressing method is used to achieve metallurgical bonding between the tantalum-containing layer and the titanium matrix implant, and the bonding strength reaches more than 15 MPa. Compared with the bonding strength range (5 MPa to 23 MPa) of hydroxyapatite coating and titanium matrix (bonding methods include radio frequency magnetron sputtering, sol-gel, and plasma spraying) that have been used in clinical practice, the bonding strength is increased by 4% to 115%. The porous tantalum layer and the titanium matrix implant are not easy to fall off, ensuring the safety and reliability of subsequent use.

[0112] Furthermore, the prepared porous tantalum layer implant material has a low elastic modulus, which can effectively avoid the stress shielding effect of existing high elastic modulus materials during implantation, and further improve the effectiveness of implantation.

[0113] It can be seen that the performance parameters of the best porous tantalum layer implant material are: pore size range of 200μm to 350μm, thickness of 520μm, porosity of 27%, elastic modulus of 56GPa, and bonding force between the porous tantalum layer and the titanium base implant of 28.2MPa. The surface morphology of the prepared porous tantalum layer implant material can be found in Figure 1 ,Depend on Figure 1 It can be seen that the pore size of the porous tantalum layer is uniform, basically between 200 μm and 350 μm.

[0114] The porous tantalum layer implant material prepared by the preparation method proposed in this application has excellent performance and can be widely used in the preparation of various medical implants. Since the porous tantalum layer is conducive to the growth of bone cells, it can be widely used in the preparation of implants for hip joints, knee joints, shoulder joints, ankle joints, etc., and can promote cell adhesion, proliferation and differentiation, and show good osteogenic activity.

[0115] The above is a detailed introduction to a porous tantalum layer implant material, a preparation method and an application thereof provided in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for general technical personnel in this field, based on the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for preparing a porous tantalum layer implant material, characterized in that: The method comprises the following steps: Step 1: Obtain iron powder, aluminum powder and tantalum powder respectively by weight percentage, mix them evenly to obtain pseudo alloy powder, wherein the weight percentage ranges of iron powder, aluminum powder and tantalum powder are 50% to 70%, 10% to 20%, and 15% to 40% respectively; Step 2: Wrapping the pseudo alloy powder on the surface of the titanium-based implant with titanium foil, placing it in a mold with the same shape as the titanium-based implant, and pressing to obtain a green body, wherein the green body includes the titanium-based implant, the pseudo alloy powder and the titanium foil; Step 3: performing hot isostatic pressing on the green body under high temperature and high pressure conditions to obtain a first component, wherein the first component includes: a titanium base implant and a pseudo alloy layer; Step 4: The first component is pickled to remove the titanium foil, iron, aluminum and metal compounds thereof in the pseudo alloy layer to obtain a porous tantalum layer implant material.

2. The method for preparing the porous tantalum layer implant material according to claim 1, characterized in that: The method further comprises: Using pure water to perform ultrasonic cleaning on the first component after the pickling treatment for multiple times to remove residual acid on the surface of the first component; The power range of the ultrasonic cleaning is 30kHz to 50kHz, and the time range is 5min to 25min.

3. The method for preparing the porous tantalum layer implant material according to claim 1, characterized in that: The weight percentages of the iron powder, aluminum powder and tantalum powder are in the range of 53% to 57%, 12% to 14% and 30% to 35% respectively.

4. The method for preparing the porous tantalum layer implant material according to claim 1, characterized in that: In step 3, the temperature range of the hot isostatic pressing treatment is 550° C. to 650° C., the pressure range is 150 MPa to 200 MPa, and the holding time range is 2 h to 4 h.

5. The method for preparing the porous tantalum layer implant material according to claim 1, characterized in that: In step 3, the temperature range of the hot isostatic pressing treatment is 630° C. to 650° C., the pressure range is 180 MPa to 200 MPa, and the holding time range is 3 h to 4 h.

6. The method for preparing the porous tantalum layer implant material according to claim 1, characterized in that: In step 4, the volume ratio of the pickling solution used for pickling the first component is: 1% to 5% hydrofluoric acid, 5% to 15% nitric acid, and 1% to 5% lactic acid, and the pickling time is 2 hours.

7. The method for preparing a porous tantalum layer implant material according to claim 1, characterized in that: In step 4, the volume ratio of the pickling solution used for pickling the first component is: 4% to 5% hydrofluoric acid, 13% to 15% nitric acid, and 4% to 5% lactic acid, and the pickling time is 2 hours.

8. A porous tantalum layer titanium-based implant material, characterized in that: The porous tantalum layer implant material is prepared according to the preparation method described in any one of claims 1-7.

9. The porous tantalum layer titanium-based implant material according to claim 8, characterized in that: The porous tantalum layer implant material includes a porous tantalum layer and a titanium base implant, the pore size range of the porous tantalum layer is 200μm to 800μm, the thickness range of the porous tantalum layer is 200μm to 1000μm, the porosity range of the porous tantalum layer is 12% to 35%, the elastic modulus range of the porous tantalum layer is 24GPa to 56GPa, and the bonding force range of the porous tantalum layer and the titanium base implant is 15.6MPa to 32.3MPa.

10. Use of the porous tantalum layer implant material according to claim 8 or 9 in preparing a tantalum layer orthopedic implant, characterized in that: The porous tantalum layer implant material is used to prepare any one of the following tantalum layer orthopedic implants: implants, bone plates, acetabular cups, hip joint implants, knee joint implants, shoulder joint implants, and ankle joint implants.